Pachycoris torridus (Scopoli) and P. klugii Burmeister: a comparative study of the genital morphology of two polychromatic Pachycorinae (Heteroptera, Scutelleridae) - Schmitz, Luís Ricardo; Barcellos, Aline (Zootaxa, 2018)
Pachycoris torridus (Scopoli) and P. klugii Burmeister are two widespread, colorful and well known neotropical Pachycorinae, with partial sympatry in southern Mexico and Central America. Both species are polychromatic, which is why they each present a long list of synonyms. However, with exception of papers describing their different color morphs, there are surprisingly few works dealing with the morphology and taxonomy of these species. This paper details for the first time the genitalia of both sexes and both species. Although some color patterns are almost identical between these species, P. klugii and P. torridus can be perfectly distinguished with basis on their internal and external genitalia.